The Relationship Between Sepsis-induced Immunosuppression and Serum Toll-like Receptor 9 Level - ATALAN ÖZLEN, NAZAN (INT INST ANTICANCER RESEARCH, 2018)
Background/Aim: Our aim was to determine serum TLR-9 levels in sepsis and evaluate the relationship between sepsis and serum TLR-9 levels. Materials and Methods: The study group consisted of 80 consecutive patients with sepsis and 100 healthy individuals. The demographic characteristics, co-morbidities and hemodynamic data of all patients were recorded. Results: TLR-9 serum levels in sepsis were statistically significantly lower compared to the control group. It was also seen that when the lactate level was >5 mmol/l in patients in the sepsis group, the serum TLR-9 levels were substantially higher. Conclusion: There is a relationship between sepsis-induced immunosuppression and serum TLR-9 levels. The host immunity system can be activated by means of TLR-9-related systems, while hyperlactatemia may play a stimulating role in the re-activation of the immune system.
Keywords: Sepsis; TLR9; immunosuppression; toll-like receptors; INFLAMMATORY RESPONSE; HOST-DEFENSE; CPG DNA; INNATE; TOLL-LIKE-RECEPTOR-9; LIPOPOLYSACCHARIDE; CONTRACTILITY; DEFINITIONS; DYSFUNCTION; PNEUMONIAE